A Crack Model Around Junctions in WC/Co Composite - POSTEK, Eligiusz Witold; SADOWSKI, Tomasz (Engineering Transactions, 2016)
WC/Co ceramic metal-matrix composites are characterized by very high mechanical properties that allow for application of the composites mostly in production of different types of cutting tools. By combining in a composite structure a phase of brittle hard wolfram carbide (WC) grains with a metallic interface of cobalt (Co) that exhibits plastic properties, a geometrically complex microstructure with significantly different mechanical properties of the combined phases is created, see Fig. 1a. The presence of the elastic-plastic interface material, i.e. Co binder, in the composite structure is the reason for initiation of technological defects – mainly material porosity. During material loading pores start to coalesce and finally one can observe creation of microcracks system distributed along interfaces. The aim of the paper is to show the previously formulated model [1], [2] of the polycrystalline composite to be extended towards cracks development around the junctions of the interfaces. The obtained numerical results indicate that in the junctions high stress concentrations were observed, which leads to crack initiation and its further unstable propagation, and finally the composite failure. Results indicate that the first crack appears close to the junction and that the load carrying capacity of the sample is overestimated if a crack model in the interfaces is not assumed.